Widespread distribution of lymphatic vessels in human dura mater remote from sinus veins - Vera Quesada, César Luis; Rao, Shreyas Balachandra; Torp, Reidun; Eide, Per Kristian (Frontiers in Cell and Developmental Biology, 2023)
Background and purpose: Previous experimental studies have shown that meningeal lymphatic vessels (MLVs) are located primarily along the walls of the dural sinus veins. Whether they are more widespread throughout human dura mater has presently not been characterized. The present study explored in humans whether meningeal lymphatic vessels may be identified remote from the sinus veins and whether they differ in the various location of dura mater. Methods: We included 15 patients who underwent neurosurgery, in whom dura mater was removed as part of the planned procedure. Tissue was prepared for immunohistochemistry using the lymphatic endothelial cell markers lymphatic vessel endothelial hyaluronan receptor 1 protein (LYVE-1), podoplanin (PDPN) and vascular endothelial growth factor receptor 3 (VEGFR3). Results: Lymphatic endothelial cell positive cells were found in dura mater at the posterior fossa (n=8), temporal skull base (n=5), frontal convexity (n=1), and cranio-cervical junction (n=1).They were most commonly seen remote from blood vessels, but also occurred along blood vessels, and seemed to be most abundant at the skull base. Conclusions: The present observations show that that human lymphatic vessels are widespread in dura mater, not solely lining the dural sinuses.